Synthesis of Benzo-Fused Cyclic Compounds via Rhodium-Catalyzed Decarboxylative Coupling of Aromatic Carboxylic Acids with Alkynes - Inai, Yasuhito; Usuki, Yoshinosuke; Satoh, Tetsuya (Synthesis, 2021)
The decarboxylative coupling of diversely substituted benzoic acids with internal alkynes proceeds smoothly in the presence of a [RhCl(cod)]2/1,2,3,4-tetraphenyl-1,3-cyclopentadiene catalyst system to selectively produce highly substituted naphthalene derivatives. The catalyst system is applicable to constructing anthracene and benzo[c]thiophene frameworks through reactions of naphthoic and thiophene-2-carboxylic acids, respectively.
Keywords: C–H functionalization; carboxylic acids; decarboxylative coupling; homologation; rhodium catalysis